Overactive bladder (OAB) in women: questionnaire based approach - Veena Ganju Malla; AmitaTuteja; Pushpa Singh (Barpeta Obstetrics and Gynaecological Society, 2020)
Objectives: We aim to study the prevalence of various lower urinary tract symptoms in women with overactive bladder (OAB). We also evaluated the impact of OAB on patient's quality of life (QOL) through various validated self reporting questionnaires. Methods: An observational cross-sectional study was done where a total of 200 patients who were confirmed cases of OAB were included in the study. The patients were questioned using four structured well designed validated questionnaires and the data were recorded and analysed. Results: Age of patients ranged from 18 to 72 years. Urine frequency (99%) was the most commonly reported symptom followed by nocturia (91%) and urgency (89%). The mean scores for American urology association symptom index (AUASI) was 17, total bothersomeness score (TBS):30.17, urogenital distress inventory (UDI) - 6:58.75 and incontinence impact questionnaire (IIQ -7) was 75.95. Higher scores in IIQ-7 and UDI-6 correlated well with negative impact on quality of life and this association was found to be statistically significant. Conclusion: This study offers an introduction to the concept of QOL assessment using short form questionnaires for patient with symptoms of OAB. Many sufferers seek to manage their symptoms by adjusting to the problem instead of seeking treatment. This has not only puts a negative impact on the quality of life of women but also puts a financial burden on society especially in the developing countries.